2021
DOI: 10.1016/j.cpa.2020.102180
|View full text |Cite
|
Sign up to set email alerts
|

Competing for the leading role: Trials in categorizing greenhouse and energy auditors

Abstract: This paper considers the inter-professional rivalries that took place as the Australian federal government attempted to register a pool of greenhouse and energy auditors and establish a multidisciplinary team structure for emissions-related reporting and trading schemes from 2007-2019. Drawing on the notions of trials (Callon 1986;Latour 1987) and criticism in trials (Bourguignon & Chiapello 2005), we show how the government's attempts in classifying and determining expert roles and responsibilities from engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This concept of a trial of strength has different meanings (Akrich et al, 2002;Callon, 1986a;Hughes, 1987;Laguecir et al, 2020;Latour, 1987;Law, 1987). Xu and Andrew (2021) found that previous studies suggest that trials of strength are associated with various types of contests, criticisms and resistance and inevitably result in continuous negotiations, compromises and identity reconstructions (Bourguignon and Chiapello, 2005;Briers and Chua, 2001;Tremblay and Gendron, 2011). In this study, we adopted Callon's (1986a) definition of the trial of strength as a contest between competing goals from the actors who oppose the kaizen network and create competing networks that mutually exist in the firm.…”
Section: Actor-network Theory Trials Of Strength and Paradoxesmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept of a trial of strength has different meanings (Akrich et al, 2002;Callon, 1986a;Hughes, 1987;Laguecir et al, 2020;Latour, 1987;Law, 1987). Xu and Andrew (2021) found that previous studies suggest that trials of strength are associated with various types of contests, criticisms and resistance and inevitably result in continuous negotiations, compromises and identity reconstructions (Bourguignon and Chiapello, 2005;Briers and Chua, 2001;Tremblay and Gendron, 2011). In this study, we adopted Callon's (1986a) definition of the trial of strength as a contest between competing goals from the actors who oppose the kaizen network and create competing networks that mutually exist in the firm.…”
Section: Actor-network Theory Trials Of Strength and Paradoxesmentioning
confidence: 99%
“…It was suggested that the kaizen project network could result in abandonment, as it tends to weaken and has been confronted with too many trials of strength (Jollands et al, 2015). Previous studies (Bourguignon and Chiapello, 2005;Briers and Chua, 2001;Tremblay and Gendron, 2011;Xu and Andrew, 2021) show the critical role of negotiation, identifying constructions and alliances play within the network built, which could be temporally due it tends to be contested at any future time (Callon, 1986a;Jeacle, 2017a). To the best author's knowledge, our study further proposes a modest contribution to the theory by presenting some suggestions to improve the kaizen process in one practical study.…”
Section: It Is Raining Ideas But Not Leaders!mentioning
confidence: 99%
“…Hence, reputed clients have started investing in technologies such as blockchain technology (Bonsón & Bednárová, 2019;Lardo et al, 2022), data analytics, artificial intelligence (AI), Robotic Process Automation (RPA) and big data (Varma et al, 2021a;Moffitt et al, 2018). Auditor's insecurity about their technology skills in a multi-disciplinary team (Smith-Lacroix et al, 2012) and the resultant power struggles (Xu & Andrew, 2021) highlight the significant role of technology in audit engagements. The reluctance of auditors to digital migration despite the reliance of accounting on eliciting trust (Jeackle & Carter, 2011) also draws attention to the interdisciplinary skillset required to conduct quality audits.…”
Section: Introductionmentioning
confidence: 99%